2012
DOI: 10.1136/annrheumdis-2011-201247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, functional and radiographic consequences of achieving stable low disease activity and remission with adalimumab plus methotrexate or methotrexate alone in early rheumatoid arthritis: 26-week results from the randomised, controlled OPTIMA study

Abstract: ObjectiveTo assess the efficacy and safety of adalimumab plus methotrexate (ADA+MTX) compared with methotrexate monotherapy in achieving stable low disease activity (LDA; disease activity score (DAS28(CRP)) <3.2 at weeks 22 and 26) and clinical, radiographic and functional outcomes in methotrexate-naive patients with early rheumatoid arthritis (RA).Methods1032 patients with active RA were randomly assigned 1:1 to ADA+MTX or placebo plus methotrexate (PBO+MTX) for 26 weeks. Treatment modifications were to be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
1
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 21 publications
9
120
1
13
Order By: Relevance
“…Meanwhile, there are some studies suggesting that starting treatment with anti-TNF+MTX in early RA may provide good clinical results even when TNF inhibitor is withheld. 63,64 Rituximab has some advantages such that it can be used in patients with a recent history of lymphoma and demyelinating disease, latent tuberculosis, and patients who live in tuberculosisendemic regions. 20,30 Risk of serious infections with rituximab is similar with other biologics, most common ones being pneumonia, cellulitis, and urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are some studies suggesting that starting treatment with anti-TNF+MTX in early RA may provide good clinical results even when TNF inhibitor is withheld. 63,64 Rituximab has some advantages such that it can be used in patients with a recent history of lymphoma and demyelinating disease, latent tuberculosis, and patients who live in tuberculosisendemic regions. 20,30 Risk of serious infections with rituximab is similar with other biologics, most common ones being pneumonia, cellulitis, and urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPLE study design and patient inclusion/exclusion criteria have been described previously 13. Briefly, patients had active RA for ≤5 years, as defined by the 1987 ACR criteria for RA 15, had reported an inadequate response to MTX, were biologics‐naive, and had a Disease Activity Score in 28 joints using the C‐reactive protein (DAS28‐CRP) level ≥3.2.…”
Section: Methodsmentioning
confidence: 99%
“…The AMPLE (Abatacept versus Adalimumab Comparison in Biologic‐Naive RA Subjects with Background MTX) trial, the first head‐to‐head trial comparing biologic DMARDs in patients with RA receiving MTX, demonstrated noninferiority for abatacept versus adalimumab by the ACR 20% improvement response (ACR20) at year 1 (64.8% subcutaneous [SC] abatacept versus 63.4% adalimumab; estimated difference between treatments 1.8% [95% confidence interval (95% CI) −5.6, 9.2] in an intent‐to‐treat analysis) 12. In AMPLE, there was a similar time of onset of ACR20 response in both treatment groups, with the response maintained up to year 2 13.…”
Section: Introductionmentioning
confidence: 99%
“…Практикующим ревматологам хорошо известны результаты рандоми-зированных контролируемых исследований, в которых доказана эффективность ГИБП в случаях неэффективно-сти/непереносимости стандартной терапии БМПП [4][5][6], в связи с чем результаты данного метаанализа вызывают некоторое удивление. Также в соответствии с рекоменда-циями EULAR (2013) по лечению ревматоидного артрита терапия ГИБП может применяться уже через 6 мес при неэффективности или непереносимости метотрексата или других небиологических БМПП при наличии небла-гоприятных факторов риска [7].…”
Section: Administration Of Tnf-␣ Inhibitors For Rheumatoid Arthritisunclassified